1994
DOI: 10.1002/j.1460-2075.1994.tb06884.x
|View full text |Cite
|
Sign up to set email alerts
|

Paramyxovirus mRNA editing leads to G deletions as well as insertions.

Abstract: Paramyxoviruses are thought to edit their P gene mRNAs co‐transcriptionally, by a mechanism in which the polymerase stutters and reads the same template base more than once. Sendai virus (SeV) and bovine parainfluenza virus type 3 (bPIV3) are closely related viruses, but SeV edits its P gene mRNA with the insertion of a single G residue (at approximately 50% frequency) within the sequence 5′ A6G3, whereas bPIV3 inserts 1 to approximately 6 Gs at roughly equal frequency within the sequence 5′ A6G4. When SeV syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…In the case of explanation (i), since the frequency of deletions or insertions in AcP2P10G viral DNA clones was statistically lower than that in AcP2P10G mRNA clones (Table 1), it is unlikely that clones with deletions or insertions were generated by errors of Taq polymerase or reverse transcriptase. Although only insertions of G residues into the editing site of hPIV2 have been reported (Ohgimoto et al, 1990 ;Southern et al, 1990), deletions as well as the insertion of G residues have been reported as a result of RNA editing in bovine parainfluenza virus type 3 and Sendai virus (Jacques et al, 1994). Our observations are consistent with these results, in that both deletions and insertions were detected.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the case of explanation (i), since the frequency of deletions or insertions in AcP2P10G viral DNA clones was statistically lower than that in AcP2P10G mRNA clones (Table 1), it is unlikely that clones with deletions or insertions were generated by errors of Taq polymerase or reverse transcriptase. Although only insertions of G residues into the editing site of hPIV2 have been reported (Ohgimoto et al, 1990 ;Southern et al, 1990), deletions as well as the insertion of G residues have been reported as a result of RNA editing in bovine parainfluenza virus type 3 and Sendai virus (Jacques et al, 1994). Our observations are consistent with these results, in that both deletions and insertions were detected.…”
Section: Discussionsupporting
confidence: 92%
“…In related paramyxoviruses, it has been shown that the P protein is required, in cooperation with the L protein, for viral RNA synthesis (Curran et al, 1993 ;Deshpande & Portner, 1985 ;Hamaguchi et al, 1983 ;Horikami et al, 1992). The Cterminal sequence of the V protein is conserved in paramyxoviruses (Thomas et al, 1988) and contains conserved cysteine residues in a motif that is homologous to the zinc- finger domains that have been identified in many transcription factors and nucleic acid-binding proteins (Jacques et al, 1994). A recent report showed that the V protein is required for pathogenesis of the virus (Kato et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This causes a +1 or +2 frameshift in the downstream ORF [10][11][12] which results in the generation of two or three distinct proteins (P, V and W/D/I), which have common N-terminal sequences but unique C-termini ( Figure 1B). A comparable editing process is used by Ebolavirus of the Filovirus family to produce isoforms from its G gene [13] .…”
Section: Paramyxovirus P Genementioning
confidence: 99%
“…This was aimed at the elucidation of cis-and trans-acting transcription factors and involved promoter mutagenesis (Engelhorn et al, 1993;Kfilin et al, 1994;Calain & Roux, 1995;Pattnaik et al, 1995;Wertz et al, 1995;Yu et al, 1995) as well as the analysis of particular properties of the virus polymerases (Jacques et al, 1994;Schnell & Conzelmann, 1996) and the virus assembly process (Kaptur et al, 1995;Mebatsion et al, 1995;Stillman et al, 1995). The approach appears to be applicable to most of the negative-strand RNA viruses, including the segmented bunyaviruses (Dunn et al, 1995;Lopez et al, 1995).…”
Section: Production Of Rnps Entirely From Cdnaencoded Componentsmentioning
confidence: 99%